Pengembangan Diri Melalui Sosialisasi Public Speaking Pada Karang Taruna Dukuh Brajan - Malik Fajar Sidik; Nur ‘Aini Purwaningsih; Viona Sebastian Nolani; Rahmat Wisudawanto; Sigit Andrianto; Esfandani Peni Indreswari (Fakultas Teknik Universitas Cenderawasih, 2023)
Karang Taruna is a youth organization in society which is used as a place for the growth and development of the young generation, which is based on awareness and social responsibility in society in the local area. In interacting between humans, good communication is certainly needed so that the message we want to convey to the person we are talking to can be received and easily understood. The method of this service is lecture and discussion. The informants or subjects in this service are members of the youth organization who are residents of Dukuh Brajan, Sindon Village. The result of this service is that public speaking outreach can provide benefits for the young people of Dukuh Brajan in forming and developing themselves. The conclusion from the service carried out by the author is that public speaking outreach can be an effort to develop the potential of the young people of Dukuh Brajan